Brief Report: Weight Gain Following ART Initiation in ART-Naïve People Living With HIV in the Current Treatment Era. (1st March 2021) - Ruderman, Stephanie A.; Crane, Heidi M.; Nance, Robin M.; Whitney, Bridget M.; Harding, Barbara N.; Mayer, Kenneth H.; Moore, Richard D.; Eron, Joseph J.; Geng, Elvin; Mathews, William C; Rodriguez, B; Willig, Amanda L.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: Evaluate differences in weight change by regimen among people living with HIV (PLWH) initiating antiretroviral therapy (ART) in the current era. Methods: Between 2012 and 2019, 3232 ART-naïve PLWH initiated ≥3-drug ART regimens in 8 Centers for AIDS Research Network of Integrated Clinical Systems sites. We estimated weight change by regimen for 11 regimens in the immediate (first 6 months) and extended (all follow-up on initial regimen) periods using linear mixed models adjusted for time on regimen, interaction between time and regimen, age, sex, race/ethnicity, hepatitis B/C coinfection, nadir CD4, smoking, diabetes, antipsychotic medication, and site. We included more recently approved regimens [eg, with tenofovir alafenamide fumarate (TAF)] only in the immediate period analyses to ensure comparable follow-up time. Results: Mean follow-up was 1.9 years on initial ART regimen. In comparison to efavirenz/tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC), initiating bictegravir/TAF/FTC 3.9 kg [95% confidence interval (CI): 2.2 to 5.5] and dolutegravir/TAF/FTC [4.4 kg (95% CI: 2.1 to 6.6)] were associated with the greatest weight gain in the immediate period, followed by darunavir/TDF/FTC [3.7 kg (95% CI: 2.1 to 5.2)] and dolutegravir/TDF/FTC [2.6 kg (95% CI: 1.3 to 3.9)]. In the extended period, compared with efavirenz/TDF/FTC, initiating darunavir/TDF/FTC was associated with a 1.0 kg (95% CI: 0.5 to 1.5) per 6-months greater weight gain, whereas dolutegravir/abacavir/FTC was associated with a 0.6-kg (95% CI: 0.3 to 0.9) and dolutegravir/TDF/FTC was associated with a 0.6-kg (95% CI: 0.1 to 1.1) per 6-months greater gain. Weight gain on dolutegravir/abacavir/FTC and darunavir/TDF/FTC was significantly greater than that for several integrase inhibitor-based regimens. Conclusions: There is heterogeneity between regimens in weight gain following ART initiation among previously ART-naïve PLWH; we observed greater gain among PLWH taking newer integrase strand transfer inhibitors (DTG, BIC) and DRV-based regimens.